2015
DOI: 10.7324/japs.2015.50406
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids and Sterols from Hoya multiflora Blume

Abstract: Chemical investigation of the dichloromethane extracts of Hoya multiflora Blume led to the isolation of lupeol (1a), α-amyrin (1b), β-amyrin (1c), lupeol acetate (2a), α-amyrin acetate (2b), and β-amyrin acetate (2c) from the stems; and 1b, bauerenol (3), squalene (4), lutein (5), β-sitosterol (6a), and stigmasterol (6b)from the leaves. The structures of 1-6 were identified by comparison of their 1 H and/or 13 C NMR data with those reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…Terpenoids such as αand βamyrin have been reported to have anti-inflammatory effects in rodents, while some authors have also reported their usefulness as painkillers and for treating inflammation (Ebajo et al, 2015;Okoye et al, 2014). These compounds in the seed oil of P. macrophylla suggest their usefulness as a painkiller and an antiinflammatory agent.…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids such as αand βamyrin have been reported to have anti-inflammatory effects in rodents, while some authors have also reported their usefulness as painkillers and for treating inflammation (Ebajo et al, 2015;Okoye et al, 2014). These compounds in the seed oil of P. macrophylla suggest their usefulness as a painkiller and an antiinflammatory agent.…”
Section: Resultsmentioning
confidence: 99%
“…Baas WJ, Berkel IEM Van, Versluis C, Heerma W, Kreyenbroek MN. 1992 Lupeol (Baas and Figdor 1978;Baas and Niemann 1979;Niemann et al 1979;Ebajo et al 2014;Ebajo, Shen, et al 2015c;Panajon et al 2016;Seeka et al 2017) Lupeol acetate α-amyrin (Baas and Figdor 1978;Niemann et al 1979;Baas et al 1992;Ebajo et al 2015b;Ebajo et al 2015c;Panajon et al 2016) α-amyrin acetate (Ebajo et al 2015c) β-amyrin (Baas and Figdor 1978;Baas and Niemann 1979;Niemann et al 1979;Baas et al 1992;Ebajo et al 2015a;Ebajo et al 2015b;Ebajo et al 2015c;Panajon et al 2016) β-amyrin acetate (Baas and Niemann 1979;Ebajo et al 2015c) β-amyrin cinnamate (Ebajo et al 2015a;Ebajo et al 2015b;Panajon et al 2016)…”
Section: Supplementary Referencesunclassified